Pola Brief Hope Intervention dalam Mengembangkan Kekuatan Harapan Siswa - Septina, Tea; Ilfiandra, Ilfiandra; Yudha, Eka Sakti (Universitas Mathla'ul Anwar Banten, 2023)
Building hope is necessary so students are not easily discouraged, fragile, and frustrated in an era of competition. Intervention on the power of hope must be given in short sessions because the z-generation is used to short processes. The research aims to describe the Brief Hope Intervention (BHI) pattern to develop students' hope power. The research was conducted using a systematic literature review method. The study results show that BHI is a modification of hope therapy that aligns with the principles of SFBC. BHI was conducted in four sessions: two face-to-face sessions (1 hour) and two follow-up sessions (30 minutes). BHI targets are 1) finding workable goals (goal setting), 2) finding ways to achieve targets (pathway), and 3) positive self-talk to optimize motivation in achieving set goals (agency). In practice, focus on the perception of development and assessment of self-strength. Counselors can use worksheets and questions directed at strengths and resources, especially relational questions.